Physico-Chemical Properties, Phytochemical Screening and Antioxidant Potential of Polar and Non-Polar Seed Extractions of Selected Medicinal Plants of Solanaceae - Ghaffar, Nausheen; Perveen, Anjum; Ijaz, shabir (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2024)
The objective of this study was to investigate the various bioactive components and assess the biological activity in the seeds of five medicinal plants (Datura innoxia Miller., Solanum elaeagnifolium Cav., Solanum nigrum L., Solanum surattense Burm., and Withania coagulans (Stocks) Dunal.) in Solanaceae family. In this regard, ash values, acid-insoluble ash and water-soluble ash values, extractive values and screening of various phytochemicals (alkaloid, carbohydrate, protein, flavonoid, tannins, saponins, and fixed oil) and quantitative estimation of carbohydrate and protein of seeds of selected plants have been calculated. The 2,2-diphenyl-1-picryl hydrazyl (DPPH) free radical scavenging assay was used to evaluate the antioxidant potential. Captivatingly, a phytochemical screening assay affirmed the presence of saponins, terpenoids, phenolic compounds, and flavonoids in the seeds of all examined plants. The highest amounts of DPPH radical-scavenging activity were found in the aqueous extract of W. coagulans (IC50 = 65.6 µg/ml). Consequently, current findings showed all selected plants of the family Solanaceae contain highly bioactive components, which could be used for the treatment of different diseases and as a potential resource for discovering new drugs.